Enhancement of oxygen permeability by copolymerization of silyl group-containing diphenylacetylenes with tert-butyl group-containing diphenylacetylene and desilylation of copolymer membranes. Issue 49 (15th June 2017) - Sakaguchi, T.; Lin, Y.; Hashimoto, T.
Abstract : The gas permeability of poly(TMSDPA- co -TBDPA) was higher than those of homopolymers, poly(TMSDPA) and poly(TBDPA). The gas permeability of copolymers and desilylated copolymers increased with increasing of the composition ratio of TBDPA. Abstract : Diphenylacetylenes having various silyl groups [PhCCC6 H4 -R; R = p -SiMe3 (TMSDPA), p -SiEt3 (TESDPA), p -SiMe2 - n -C8 H17 (DMOSDPA), and p -SiPh3 (TPSDPA)] were copolymerized with diphenylacetylene having a tert -butyl group (PhCCC6 H4 - tert Bu; TBDPA) using a TaCl5 – n -Bu4 Sn catalyst in various monomer feed ratios to provide high-molecular-weight copolymers in high yields. The free-standing membranes were fabricated by solution-casting, except poly(TPSDPA- co -TBDPA). Interestingly, the gas permeability of poly(TMSDPA- co -TBDPA) was higher than those of the homopolymers, poly(TMSDPA) and poly(TBDPA). The permeability of the copolymers became lower as the silyl groups became bulkier. The desilylation of membranes was carried out using a mixture of trifluoroacetic acid/hexane. When bulkier silyl groups were removed, the oxygen permeability increased to larger extents. The oxygen permeability coefficients of the copolymers and desilylated copolymers increased with increasing composition ratio of TBDPA. The gas diffusivity and gas solubility were also increased upon desilylation.